Understanding individual heat exposure through interdisciplinary research on thermoception - Paloma Yáñez Serrano; Zofia Bieńkowska; Zofia Boni; Franciszek Chwałczyk; Amirhossein Hassani (Humanities & Social Sciences Communications, 2024)
Abstract Extreme heat events are more frequent and more intense globally due to climate change. The urban environment is an additional factor enhancing the effects of heat. Adults above 65 years old are especially at risk due to their poorer health, physiology and socio-economic situation. Yet, there is limited knowledge about their experiences of summer heat, their actual heat exposure and how they negotiate their thermal comfort through different adaptation practices. In conventional research on heat exposure and thermal comfort, very little attention is given to individual behaviour and subjective experiences. To understand how older adults feel the heat in the city we study their thermoception, which we conceptualise as an embodied knowledge about bodily sensations, thermal environments and adjustments to heat. This article stems from interdisciplinary research conducted in Warsaw and Madrid in the summers of 2021–2022. We combine and juxtapose data from ethnographic research and from physical measurements of temperature gathered in people’s homes, to show on a microscale how we can study and understand the diversity in individual heat exposure more holistically. We demonstrate that to understand the consequences of heat for vulnerable populations it is crucial to study thermoception, the subjective experiences of heat, in addition to analysing their thermal environments. With the use of a unique methodology, this article shows how similar weather conditions are experienced differently by people from the same cities, depending on the materiality of their dwellings, availability of cooling devices, as well as everyday habits and their individual bodies. We discuss the social, material and temporal adjustments participants made to deal with heat, to showcase their agency in affecting their individual heat exposure. The article emphasises the role of social sciences and qualitative methods in research on individual heat exposure and argues for the co-production of knowledge on the topic.